Effect of Strenuous Arm Exercise on Oxidized-LDL-Potentiated Platelet Activation in Individuals with Spinal Cord Injury - Wang, Jong-Shyan; Yang, Chih Fang; Wong, May-Kuen; Chow, Shu-Er; Chen, Jan-Kan (Thrombosis and Haemostasis, 2000)
This study investigates how strenuous arm exercise affects oxidizedlow density lipoprotein (Ox-LDL) mediated-platelet activation in patients with SCI. Ten patients with SCI and ten age- and sex-matched healthy subjects exercised strenuously using an arm crank ergometer. The following measurements were taken both when the subjects were at rest, and immediately after exercise: plasma lipid profile, Ox-LDL mediated platelet aggregability and [Ca2+]i, urinary 11-dehydro-thromboxane B2 (11-dehydro-TXB2) and 8-iso-prostaglandin F2α. (8-iso-PG F2α.) contents, and plasma NO metabolite (nitrite plus nitrate) level. Based on these measurements, the major findings of this study can be summarized as follows: 1) the SCI group had higher urinary 8-iso- PGF2α. and 11-dehydro-TXB2 contents, but a lower plasma nitrite plus nitrate level than the control group; 2) at rest, the SCI group had a higher platelet aggregability and [Ca2+]i, and Ox-LDL-potentiated platelet activation than the control group; 3) Ox-LDL-potentiated platelet aggregation was enhanced by strenuous arm exercise in both groups, but the effect of exercise was more pronounced in the SCI group than in the control group; 4) treating the platelet with L-arginine inhibited Ox-LDL-potentiated platelet activation in both groups. The study concludes that individuals with SCI had more extensive resting and exercise-enhanced Ox-LDL-potentiated platelet activation and greater amounts of preformed lipid peroxides than those without SCI. Therefore, supplementation therapy with antioxidants may be needed for patients with SCI, especially in a strenuous arm exercise period.
Keywords: SCI; exercise; platelet; nitric oxide; Ox-LDL